Utility of Germline, Somatic and ctDNA Testing in Adults With Cancer - Emily DeBortoli; Ella McGahan; Tatiane Yanes; Jennifer Berkman; Lauren G. Aoude; Amelia K. Smit; Akira Gokoolparsadh; Azure Hermes; Lyndsay Newett; Mackenzie Bourke; Susan Hanson; Helen Hughes; et al. (Cancer Medicine)
ABSTRACT Background and Aim Historical genetic sequencing of specific cancer variants has been superseded by comprehensive genomic profiling (CGP). This narrative review aimed to capture current international evidence on the clinical utility of CGP for cancer prevention, detection and treatment. Materials and Methods A literature search of three databases was performed to identify key studies on the frequency of germline and somatic variants in adult cancers and the extent to which they inform diagnosis, management and outcome. Findings were inductively mapped and narratively synthesised. Results Consolidated results from 95 original research papers showed that pathogenic germline (familial) variants are found in ~10% of adults with cancer, of whom 53%–61% are offered germline genotype‐directed treatment. Importantly, 50% of germline carriers would not have satisfied the eligibility criteria for genetic testing and/or reported a negative family history. Actionable somatic variants occur in 27%–88% of cases, which markedly impact the diagnosis for cancers of unknown primary. Matched treatments were identified for 31%–48% of cancer patients, of whom 33%–45% received it. Response and survival rates were better in individuals receiving matched therapies compared to those receiving standard of care or unmatched therapies. Trials show that circulating tumour DNA (ctDNA) assays are feasible and sensitive. The relatively non‐invasive ctDNA sample collection is appealing for cancers with inaccessible or unknown primary sites, and serial monitoring of residual disease and/or treatment response. Conclusions As matched therapies are underutilised due to declining patient condition and fewer prior therapies predicting better response rates, research is needed on the suitability of cancer genomic profiling as a frontline test.